Factor influencing after hours Attendances in the mosque road polyclinic and emergency department, Sarawak General Hospital, Kuching - Johnny, Pangkas (Universiti Malaysia Sarawak (UNIMAS), 2011)
~ttendance for non urgent cases during the after office hours is high in the emergency department and this had lead to the introduction of extended hours service in the polyclinic. Currently there are no study done in Kuching to determine the reasons for these attendances in the emergency department and polyclinic. The objective of the this study is to determine the reasons for seeking care during after-hours in the Mosques Road Polyclinic and the Emergency Department, Sarawak General Hospital, Kuching. This study was conducted through a cross sectional study and the data were obtained through a self administered questionnaire. The respondents were obtained by convenient random sampling. The self administered questionnaire was developed based on the literature revie0 The questionnaire was used to obtain data on social demographic, presenting complaints, knowledge on services in the emergency department and polyclinic, health seeking attitude and also the preferred health services. A convenient random sampling w.as done and a total of 216 respondents were obtained, comprising of 108 each from the polyclinic and the emergency department. The questionnaire was given to those who attended the polyclinic and emergency department after 5.00 pm. The data was analyzed using the SPSS version 17. The social demography shows that the mean age was 32.08 years (SD: ±1O.845). The educational background was mainly secondary school (59.62%) and most of the respondents work in the private sectors (37.50%) . .' From this study the main reason for seeking care during after-hours were the working commitment during daytime (67.6%) and also the need for accompaniment to the health facilities (50.0%). Condition getting worse only contribute 27.8% of the reason seeking care for after hours. Less traffic, shorter waiting time, parking and conditions of the illnesses showed significance differences for the reasons of attending after-hours between the two facilities. The knowledge on the services provided by these two departments showed the mean score were 5.07 and only 98 (45.8%) scored more than 5.07. From this study it also showed that 54.2% of the respondents score less than 5.07 which mean that the knowledge on the services was poor among those who attended the facilities during the study. In this study, those who attended the emergency department preferred the emergency department due to the availability of the doctors for 24 hours (89.4%) and the various investigations in the department (78.9%). Working during the day was the main factor for people attending the emergency department and polyclinic during the after-hours. The poor knowledge of the respondent's on services in the emergency department and polyclinic may contribute to the non urgent attendances in the emergency department. It is noted that patient still considered their first choice of health facilities .